Canada's Model Forests 20 years on: towards forest and community sustainability?. (August 2017) - Bullock, Ryan; Jastremski, Kathryn; Reed, Maureen G.
Abstract : We review how Canadian Model Forests pursued forest and community sustainability over the course of two decades (1992–2012). Given its roots in the forest industry and forest science, Model Forest programming initially faced some challenges in pursuing the socio‐economic dimensions of sustainable forest management (SFM) in order to fulfil mandated community sustainability objectives. This was due, in part, to how objectives, stakeholders, and expertise were brought together to develop SFM. The programme helped to define sustainability and the SFM paradigm, advance forest science and social research, and bring together a mix of usually adversarial partners in the name of innovation. Ultimately, the termination of federal programming was linked to high‐level policy shifts, yet difficulty in delivering on the socio‐economic dimensions of SFM during a period of forest sector and community crisis was also a factor.